Efficient in vitro regeneration and Agrobacterium mediated transformation protocol of an elite tomato cultivar (Solanum lycopersicum cv Pusa Gaurav) - Barthakur, Sharmistha (Annals of Agricultural Research, 2014)
An efficient and simple protocol for regeneration and transformation of an elite commercial tomato cultivar Pusa Gaurav was optimized. The effect of various factors in the regeneration medium and on explant expansion was analyzed. Four different plant growth regulator combinations of cytokinin and auxin as well as several Agrobacterium tumefaciens strains harboring the binary vectors BinAR and pBI121 were studied. All the hormone combinations worked well in plantlet regeneration in MS medium with B5 vitamins with variations in tissue culture duration till complete plantlet regeneration. BAP 2.5 and IAA 0.25 mg/L were found best with 45% regeneration and 40% transformation frequency with total duration of four months on average to generate a full plant. The Agrobacterium strain GV2260 showed the highest transformation efficiency. Transformation was confirmed by molecular analyses for presence and expression of transgenes. All the experiments were carried out during the period 2007-2009 in a laboratory study at NRCPB, New Delhi. The result establishes a very good transformation protocol for tomato cv Pusa Gaurav.